2008
DOI: 10.1002/cyto.b.20460
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the choice of monoclonal antibodies for recovery of fetal cells from maternal blood using FACS for noninvasive prenatal diagnosis of hemoglobinopathies

Abstract: Background: Isolation of adequate numbers of fetal cells circulating in the maternal circulation is the major hurdle in developing noninvasive prenatal diagnostic procedures. We used flow cytometry and a combination of different monoclonal antibodies to compare the yield and purity of the fetal nucleated red blood cells at different periods of gestation.Methods: Using a Percoll discontinuous gradient, the fetal nucleated erythrocytes were enriched from 7 ml maternal blood. In 100 samples, the enriched cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…Maternal red blood cells can be removed by bulk separation or density gradient centrifugation using Ficoll [43][44][45][46] or Percoll [47][48][49][50] in different gradient combinations, to separate the nucleated cell fraction (including fetal cells) from the maternal RBC and plasma fraction. That said, using Ficoll could result in 60%-80% fetal cell loss, 51 making the use of less aggressive methods more desirable.…”
Section: Fetal Nucleated Red Blood Cellsmentioning
confidence: 99%
“…Maternal red blood cells can be removed by bulk separation or density gradient centrifugation using Ficoll [43][44][45][46] or Percoll [47][48][49][50] in different gradient combinations, to separate the nucleated cell fraction (including fetal cells) from the maternal RBC and plasma fraction. That said, using Ficoll could result in 60%-80% fetal cell loss, 51 making the use of less aggressive methods more desirable.…”
Section: Fetal Nucleated Red Blood Cellsmentioning
confidence: 99%
“…Many different positive and negative enrichment strategies have been explored, including positive enrichment by MACS with monoclonal antibodies to CD71 or glycophorin A (Gly A) or detection by FACS using monoclonal antibodies to fetal hemoglobin (HbF). Some examples are the work of Martel-Petit et al, who identified a fetus with cystic fibrosis by studying fnRBCs [ 39 ], and Souza et al, who used a combination of antibodies to increase the specificity of fnRBC selection [ 40 ].…”
Section: Technical Approaches For Isolation or Enrichment Of Fetal Cellsmentioning
confidence: 99%
“…The large NIFTY trial utilized antibodies targeting either HbF, HbF and CD45, or CD71, but the study resulted in poor detection rates of aneuploidies and the correct fetal gender [4]. In 2009, a comparison between different enrichment antibodies was pursued by Souza et al who found that a combination of antibodies targeting CD45, HbF and CD71 yielded the highest specificity of fetal nRBCs but also a lower number of fetal cells, still leaving the use of nRBCs in cbNIPD with limited success [12]. Christensen and colleagues found that embryonic hemoglobin is more specific toward fetal nRBCs than HbF [13], but the group also concluded that only a small fraction of circulating fetal cells are of erythroblastic origin and therefore not the optimal cell type for cbNIPD [13,14].…”
Section: Fetal Cell Type and Markersmentioning
confidence: 99%